2018
DOI: 10.3390/su10093215
|View full text |Cite
|
Sign up to set email alerts
|

Open Innovation and Social Big Data for Sustainability: Evidence from the Tourism Industry

Abstract: This paper aims to contribute to the debate on Open Innovation in the age of Big Data by shedding new light on the role that social networks can play as enabling platforms for tourists’ involvement and sources for the creation and management of valuable knowledge assets. The huge amount of data generated on social media by tourists related to their travel experiences can be a valid source of open innovation. To achieve this aim, this paper presents evidence of a digital tourism experience, through a longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 57 publications
1
58
0
4
Order By: Relevance
“…The global increase in competitiveness in the tourism industry could allow the implementation of eco-innovations as an element of differentiation between the destinations and the companies that make up the industry, with quality management and sustainable development being increasingly important [146]. Another source of potential innovation could be the use of technologies that are specific to Industry 4.0 such as intelligent devices, that can help us learn about the travel experience of tourists, which are already utilised by hotels [147], Augmented Reality applied to mobile phones [148] so that tourists can take virtual tours of the destinations, "intelligent" hotels to replace personal contacts [149] (in order to protect them from COVID-19 infection, for example), or Big Data to analyse sustainable tourism experiences in the destinations [150]. However, since a lack of innovation implies a lack of adaptation to change, and when changes in the environment and in demand are as drastic as those that are required to adapt tourism businesses to the COVID-19 pandemic, the lack of adaptation and innovation puts the survival of a company at serious risk.…”
Section: Discussionmentioning
confidence: 99%
“…The global increase in competitiveness in the tourism industry could allow the implementation of eco-innovations as an element of differentiation between the destinations and the companies that make up the industry, with quality management and sustainable development being increasingly important [146]. Another source of potential innovation could be the use of technologies that are specific to Industry 4.0 such as intelligent devices, that can help us learn about the travel experience of tourists, which are already utilised by hotels [147], Augmented Reality applied to mobile phones [148] so that tourists can take virtual tours of the destinations, "intelligent" hotels to replace personal contacts [149] (in order to protect them from COVID-19 infection, for example), or Big Data to analyse sustainable tourism experiences in the destinations [150]. However, since a lack of innovation implies a lack of adaptation to change, and when changes in the environment and in demand are as drastic as those that are required to adapt tourism businesses to the COVID-19 pandemic, the lack of adaptation and innovation puts the survival of a company at serious risk.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lot of tourism research, but as Xiao and Smith [30] have pointed out, one of the major limitations of research in tourism is caused by the fact that the research is, in most cases, concerned with a single case, location, nationality, etc. Examples of such research can be found in the work of e.g., Soybali [31], Raun et al [32], Peng et al [33], Del Vecchio et al [34] and Guilarte and Quintans [35]. The scientific publications presented in Table 1 indicate that work is focused on the use of databases in order to develop methods and tools demonstrating the spatial diversity of tourism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, BDA capabilities share an essential and complementary feature with co-innovation: they are managed via technological platforms, both of which are naturally ingrained to the use that the company makes of technology with the aim of improving and generating greater value and building and maintaining competitive advantage over time (Del Vecchio et al., 2018); such complementarity is concerned with the potential of BDA capabilities to improve performance in the co-innovation process.…”
Section: Theorymentioning
confidence: 99%